National-Language Orientation in Teaching The Russian Language to Foreign Students at a Medical University - Kamila, Mamedova; Tuychievna, Razykova Lola (Journal of Higher Education and Academic Advancement, 2024)
The article deals with the problem of intensifying the process of teaching foreign students the Russian language at the pre-university stage through the use of a nationally oriented methodology for teaching Russian as a foreign language, relying on the native language as a way to improve the quality of teaching the Russian language.